Penyelundupan Narkotika Nontraditional Syndicated di Asia Tenggara dan Oceania - Catur P, Dimas Putra (RechtIdee, 2023)
The era of globalization and increasingly sophisticated and rapidly developing technology supports the circulation of narcotics by means of smuggling easier to enter other countries, including Indonesia. The increasing factor of narcotics smuggling, especially from Southeast Asia and Oceania, is studied from social disorganization, and the steps taken by the Indonesian government in tackling and minimizing narcotics smuggling crimes that occur transnationally. By taking doctrinal research, where related to this research using a normative juridical legal research method will provide an overview of the object of research and help the author to make an analysis of the correct conclusions. Countries in Southeast Asia and Oceania that experience enormous impacts in addition to environmental conditions, dense population development economies encourage the rise of narcotics business associated with the theory of social disorganization, and supported by criminal organizations as non-traditional syndicates